Lawrence P. Conover, Revised Ordinances of the Village of Hinsdale, Illinois 1912, at 168-69 (1912) - (:unkn) unknown (My University, 1912)
Chapter 26-Concealed Weapons, §§ 1-8. Undated: Prohibited concealed carry of any pistol, colt, slung-shot, cross knuckles, knuckles of lead, brass, or other metal, or Bowie-knife, dirk, dagger, or other dangerous or deadly weapon. Violators shall have weapons confiscated, arrested before a warrant is issued, fined not less than five nor more than two hundred dollars.
Keywords: CARRY - CONCEALED